"CME" series of Taijiquan teaching mode research - Hu, Zhongjie; Xie, Lei (The Journal of the International Society of Chinese Health Practices, 2021)
The medical Sports Training Department of the third people's hospital directly under Henan Province is a professional department engaged in the integration of sports and medicine and the study of Taijiquan and health. In recent years, it has accumulated rich experience in the application of scientific sports in prevention of disease, sub-health intervention, rehabilitation and health preservation. In order to make more people understand Taijiquan, give full play to the unique advantages of Taijiquan in bodybuilding, fitness and mental health, and actively participate in the health action plan to promote scientific sports, 14 primary fitness classes of Chen's Taijiquan have been held to share Taiji and health. Objective: "stand for half a year, walk your legs for half a year" and "Tai Chi doesn't go out for ten years". In order to solve the problems of difficult learning, time-consuming and pain (knee injury) in the process of learning Tai Chi, the medical training center of the third people's hospital directly under Henan Province studied and analyzed more than 300 people in the 14 primary fitness classes of Tai Chi, and summarized a set of methods to solve the problems of difficult learning, time-consuming and Taijiquan Teaching Model for pain (knee injury) and other problems. Methods: the article combs and summarizes the research on the teaching mode of Chen zhenglei's Taijiquan system by using the methods of combing, comparison, refining, reflection and induction. The 14 classes are divided into two groups for comparative test. The first 7 classes are taught by the traditional Chen's Taijiquan teaching mode, and the last 7 classes are taught by the "CME" series teaching mode, Check the difficulty, falling behind, pain, learning speed and understanding of Taijiquan of the two groups. Results: the new "CME" series Taijiquan teaching mode will make our practice easier, easier, time-saving, healthier and less likely to be injured. Conclusion: through the comparative research and analysis of the new "CME" series Taijiquan teaching mode for more than 300 people in 14 periods, this theory can perfectly avoid the problems of difficult learning and practice, time-consuming and pain (knee injury) in Taijiquan, and achieve the following three therapeutic purposes: first, treatment: bone and tendon are soft (numbness and swelling in the hand, fever in the palm and heavy feeling in the forearm); Relieve the symptoms of neck, shoulder, waist and leg pain, not easy to fatigue, strong body, vigorous energy, stable mood and good sleep; second, Disease prevention: spontaneous flow of Qi and blood; Small and large-scale communication, enhanced balance ability, enhanced fall prevention ability, and no neck, shoulder, waist and leg pain; Improved cardiovascular and digestive functions, smooth and delicate skin, soft and flexible body (increased rebound rate); Lastly, Longevity: ten years longer; Channels and collaterals are connected, viscera are flat, body and mind are unified, heaven and man are one, and body and mind are healthy.